Implementation of Educational Human Resource Management In Improving The Quality of Learning - Ricky Firmansyah; Ade Mubarok; Ai Nurhasan; Agus Sutardi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to identify, analyze, and synthesize research findings on the implementation of human resource management (HRM) in education to improve learning quality. This study employed a Systematic Literature Review (SLR) approach using the PRISMA method. The data were obtained from 20 journal articles, indexed in Sinta and Scopus, published within the last five years, and selected for their relevance to educational HRM and learning quality. The findings show that educational HRM plays an important role in improving learning quality. However, its implementation remains limited and has not been fully integrated. The main issues include weak HR planning, non-competency-based recruitment, limited continuous professional development, and ineffective teacher performance evaluation. In addition, digitalization in the Education 4.0 era creates new challenges, particularly in preparing teachers to integrate technology into learning. The novelty of this study lies in its systematic synthesis of problem patterns, research trends, and gaps in educational HRM implementation, particularly in relation to teacher readiness and the improvement of learning quality. This study contributes by providing a comprehensive literature-based framework that can serve as a basis for future research and the development of more integrated HRM practices in education.